First‐line treatment with FOLFOXIRI for advanced pancreatic cancer in clinical practice: Patients' outcome and analysis of prognostic factors. Issue 4 (18th April 2016) - Vivaldi, Caterina; Caparello, Chiara; Musettini, Gianna; Pasquini, Giulia; Catanese, Silvia; Fornaro, Lorenzo; Lencioni, Monica; Falcone, Alfredo; Vasile, Enrico
Abstract : FOLFIRINOX is a standard first‐line treatment for advanced pancreatic cancer (aPC). The Gruppo Oncologico Nord Ovest (GONO) FOLFOXIRI regimen demonstrated efficacy in metastatic colorectal cancer. We aimed to evaluate activity and tolerability of FOLFOXIRI regimen in patients with aPC and to explore putative prognostic factors. One hundred thirty‐seven consecutive aPC patients were treated with FOLFOXIRI in our institution between 2008 and 2014. Clinical, laboratory and pathological data were collected and their association with activity, progression free survival (PFS) and overall survival (OS) was investigated. After a median follow up of 30 months, median PFS and OS were 8.0 months (95% CI 6.19–9.81) and 12 months (95% CI 9.75–14.25), respectively. Response rate was 38.6%, while disease‐control rate 72.2%. At multivariate analysis liver metastases ( p  = 0.019; Hazard Ratio, HR, 0.59, 95% Confidence Interval, CI, 0.380.96), Eastern Cooperative Oncology Group (ECOG) performance status (PS) 1 ( p  = 0.001; HR 2.26, 95%CI 1.42–3.59) and neutrophil‐lymphocyte ratio (NLR)> 4 ( p = 0.002; HR: 2.42; 95% CI 1.38–4.25) were associated with poorer OS. We categorized 119 pts with complete available data as good‐risk (0 factors, 38 pts), intermediate‐risk (1 factor, 49 pts) and poor‐risk (≥2 factors, 32 pts). Median OS for these three groups were 17.6, 11.1 and 7.4 months, respectively ( p  < 0.001). FOLFOXIRI is active and feasible in aPC. Prognosis of aPC pts treated with FOLFOXIRI is influenced by easily available factors: our analysis revealed ECOG PS, liver metastases and NLR as the most important predictors of survival. These factors could be helpful for treatment decision and clinical trial design. Abstract : What's new? Standard first‐line therapy for advanced pancreatic cancer centers on FOLFIRINOX, a combination regimen using 5‐fluorouracil, irinotecan, oxaliplatin, and gemcitabine plus nabpaclitaxel. The regimen's increased adverse effects, however, warrant investigation of alternative drug combinations. Here, modified Gruppo Oncologico Nord Ovest FOLFOXIRI (5‐fluorouracil, leucovorin, irinotecan and oxaliplatin) was found to produce survival results similar to those of FOLFIRINOX in patients with pancreatic cancer. The modified FOLFOXIRI regimen also compared favorably with FOLFIRINOX in terms of gastrointestinal adverse events. Prognostic factors were identified, enabling FOLFOXIRI‐treated patients to be stratified into subgroups with different survival outcomes.